Detecting method for an open-switch fault of SiC MOSFET and Si IGBT in hybrid ANPC inverter system - Kwon, Bong Hyun; Bae, Kyu Chul; Kim, Seok Min; Lee, Kyo Beum (2019 IEEE Energy Conversion Congress and Exposition, ECCE 2019, 2019)
This paper presents an open fault detection method for hybrid active neutral-point-clamped (ANPC) inverter under the grid-connected systems. The proposed method can detect the faulty condition and identify the location of faulty active switches. In case an open fault occurs in the active switches of the hybrid ANPC inverter, current pattern and vector angle are distorted. By applying the proposed method with simple injection of voltage vector, the open switch faulty condition is detected on the radius of the current pattern. The faulty condition and the exact location of faulty device can be detected within two cycle of fundamental wave without performing complex calculations or using additional sensors. The simulation results by applying the proposed detection algorithm for a hybrid ANPC inverters are provided to verify the performance and feasibility.
Keywords: Fault detection; Grid-connected inverter; Hybrid active neutral-point clamped (ANPC) inverter; Open switch fault; Reliability